2008
DOI: 10.1007/s10549-008-0263-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical proteomics in breast cancer: a review

Abstract: Breast cancer imposes a significant healthcare burden on women worldwide. Early detection is of paramount importance in reducing mortality, yet the diagnosis of breast cancer is hampered by the lack of an adequate detection method. In addition, better breast cancer prognostication may improve selection of patients eligible for adjuvant therapy. Hence, new markers for early diagnosis, accurate prognosis and prediction of response to treatment are warranted to improve breast cancer care. Since proteomics can bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 88 publications
0
57
0
3
Order By: Relevance
“…As shown in Figure 2, cells treated with fluopsin C (0.5 to 8 μmol/L) for different times (6,12, and 24 h) exhibited a decrease in viability in a dose-and time-dependent manner. The IC 50 values were 2.9, 1.6, and 0.9 μmol/L for MCF-7 cells and 2. μmol/L at 6, 12, and 24 h, respectively), suggesting the necessity of investigating the anticancer activity of fluopsin C and considering its toxicity in future clinical use and drug development.…”
Section: Fluopsin C Cytotoxicitymentioning
confidence: 89%
“…As shown in Figure 2, cells treated with fluopsin C (0.5 to 8 μmol/L) for different times (6,12, and 24 h) exhibited a decrease in viability in a dose-and time-dependent manner. The IC 50 values were 2.9, 1.6, and 0.9 μmol/L for MCF-7 cells and 2. μmol/L at 6, 12, and 24 h, respectively), suggesting the necessity of investigating the anticancer activity of fluopsin C and considering its toxicity in future clinical use and drug development.…”
Section: Fluopsin C Cytotoxicitymentioning
confidence: 89%
“…Irrespective of the different clinical setting and technical approach, most of these analyses found an association between several known proteins or their fragments, such as diverse apolipoproteins, complement factors, fibrinogen and haptoglobin. Many of these have been shown not to be disease-specific, and none have been validated in a prospective clinical study (25). the most differentiating proteins, based on their relative importance of the peak value in the classification between gastric cancer patients and matched normal control subjects (table IV), varied on different days of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…(70) demonstrated that cell lines of human cancer which increased expression of 14-3-3σ contributed to drug resistance, suggesting that such a change is associated with clinical resistance to chemotherapy. In treatments stimulating apoptosis, ubiquitin and S100-A6 decreased in the lysates of breast cancer cell lines, and aberrant expression of the two proteins in breast cancer tissue was found (71). In recent studies, a proteomic analysis of 14 matched pairs of tumor tissues (ER-positive) prior to and following neoadjuvant treatment with aromatase inhibitor (AI) revealed 10 differentially expressed proteins.…”
Section: Prognostic and Predictive Marker Protein Profiling Studiesmentioning
confidence: 99%